Sodium ferric phosphate pyrophosphate composite material, preparation method and application thereof, and sodium ion battery

The compaction and porosity problems of the sodium ferropyrophosphate positive electrode material were solved by solid phase mixing method, and the electrochemical performance and cell processing performance of the material were significantly improved.

CN119284857AInactive Publication Date: 2025-01-10四川易纳能新能源科技有限公司

Patent Information

Application Number
CN202411430328.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ferric pyrophosphate positive electrode materials have poor compaction performance, high powder resistance, and carbon source coating methods have problems such as uneven distribution and difficult to reduce porosity, which affects the processing performance of the battery cell and the overall performance of the battery.

Method used

The carbon-coated sodium ferric pyrophosphate phosphate and an organic carbon source were subjected to secondary sintering treatment, with a temperature ranging from 400℃-580℃, a temperature increase rate of 1℃/min-8℃/min, and a insulation time of 0.5h -3h, through secondary carbon source sintering and coating, the defect of uneven coating of primary carbon source is compensated, the powder resistance and porosity are reduced, and the surface water resistance is enhanced.

Benefits of technology

It significantly improves the compaction and electrochemical properties of the material, reduces the loss of active sodium ions, and improves the processing performance of the battery cell and the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284857A_ABST
    Figure CN119284857A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ferric phosphate pyrophosphate composite material, a preparation method and application thereof, and a sodium ion battery, and relates to the technical field of positive electrode materials, the preparation method comprises the following steps: carrying out solid phase mixing on carbon-coated sodium ferric phosphate pyrophosphate and an organic carbon source, and then carrying out sintering treatment to obtain the sodium ferric phosphate pyrophosphate composite material; the temperature of the sintering treatment is 400-580 DEG C. The technical problems that in the prior art, according to a carbon source coating method, carbon source coating is not uniform, the porosity between materials is difficult to effectively reduce, the compaction performance of the materials cannot be remarkably improved, and the crystal structure of the materials is prone to change are solved, and the purposes of reducing the powder resistance of the materials and improving the compaction performance of the materials are achieved. The carbon coating uniformity is effectively improved, the porosity of the material is effectively reduced, the compaction performance of the material is remarkably improved, the water absorption of the material is reduced, and the crystal structure of the material is improved, so that the technical effect of comprehensively improving the performance of the material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a sodium iron phosphate pyrophosphate composite material, a preparation method thereof, an application thereof, and a sodium ion battery. Background Art

[0002] Sodium ferric pyrophosphate (Na x Fe y (PO4) z P2O7) is a new type of battery positive electrode material with the advantages of high energy density, long cycle life and environmental friendliness. It is widely used in electric vehicles and energy storage systems. However, the compaction performance of this material is poor and the powder resistance is high, which seriously affects the processing performance of the battery core and the overall performance of the battery. To solve the above problems, the existing technology usually uses a carbon source coating method to modify the material. x Fe y (PO4) z After the P2O7 material is mixed evenly, it is sintered at a high temperature, so that the carbon source is carbonized during the sintering process to form a carbon coating layer, thereby reducing the powder resistance of the material and improving its compaction performance.

[0003] However, the carbon source coating method used in the prior art often has the following problems: first, due to the uneven distribution of the carbon source, the coating effect may be poor, thereby affecting the performance of the material; second, although the powder resistance of the material can be reduced by carbon source coating, the porosity between the materials cannot be effectively reduced, so it is difficult to significantly improve the compaction performance of the material; in addition, the existing sintering process may cause the material to have strong water absorption in the air, resulting in the loss of active sodium ions, affecting its electrochemical performance.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a sodium iron phosphate pyrophosphate composite material, which has a simple process, high efficiency and high success rate. It can not only improve the uniformity of carbon source coating, effectively reduce the powder resistance and porosity of the material, and significantly improve the compaction performance of the material, but also enhance the surface water resistance of the material and reduce the loss of active sodium ions, thereby comprehensively improving the performance of the material.

[0006] The second object of the present invention is to provide a sodium iron phosphate pyrophosphate composite material having the characteristics of high compaction and high conductivity.

[0007] The third object of the present invention is to provide an application of a sodium iron phosphate pyrophosphate composite material, which is beneficial to improving the processing performance of the battery cell and the overall performance of the battery.

[0008] A fourth object of the present invention is to provide a sodium ion battery with excellent working performance.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In a first aspect, a method for preparing a sodium iron phosphate pyrophosphate composite material comprises the following steps:

[0011] The carbon-coated sodium iron phosphate pyrophosphate is solid-phase mixed with an organic carbon source and then sintered to obtain the sodium iron phosphate pyrophosphate composite material;

[0012] The sintering temperature is 400°C-580°C.

[0013] Furthermore, the heating rate of the sintering process is 1°C / min-8°C / min;

[0014] The holding time of the sintering treatment is 0.5h-3h.

[0015] Furthermore, the sintering temperature is 500°C.

[0016] Furthermore, the chemical formula of the carbon-coated sodium iron pyrophosphate is as follows:

[0017] Na x Fe y (PO4) z P2O7@C;

[0018] Among them, x is between 3-6, y is between 2-5, and z is between 1-4.

[0019] Furthermore, the preparation method of the carbon-coated sodium iron phosphate pyrophosphate comprises the following steps:

[0020] The sodium source, the iron source, the phosphorus source and the carbon source are mixed and sand-milled and then spray-dried to obtain a precursor, and the precursor is calcined to obtain carbon-coated sodium iron phosphate pyrophosphate.

[0021] Furthermore, the particle size after sand grinding is 100nm-1000nm.

[0022] Furthermore, the organic carbon source includes at least one of glucose, starch, citric acid, vitamin C, polyethylene glycol, phenolic resin, polystyrene and sucrose.

[0023] In a second aspect, a sodium iron phosphate pyrophosphate composite material is prepared by any of the preparation methods described above.

[0024] In a third aspect, an application of the above-mentioned sodium iron phosphate pyrophosphate composite material in a battery positive electrode material.

[0025] In a fourth aspect, a sodium ion battery is provided, wherein the positive electrode of the sodium ion battery comprises the sodium iron phosphate pyrophosphate composite material described above.

[0026] Compared with the prior art, the present invention has at least the following beneficial effects:

[0027] The preparation method of the sodium iron phosphate pyrophosphate composite material provided by the present invention comprises the following steps: solid-phase mixing carbon-coated sodium iron phosphate pyrophosphate (which can be understood as a sodium iron phosphate pyrophosphate material formed by sintering and coating a primary carbon source) with an organic carbon source, and then sintering treatment (which can be understood as secondary carbon source sintering and coating) is performed to obtain the sodium iron phosphate pyrophosphate composite material; on the one hand, after the secondary carbon source sintering and coating, the specific surface area of ​​the obtained composite material does not increase with the increase of carbon content, so that no side effects are produced on the processing of the battery core; on the other hand, through the secondary carbon source sintering and coating, It can make up for the defects of uneven primary carbon source coating, reduce the powder resistance of the material, effectively improve the uniformity of carbon coating, thereby improving the performance of the material, and the repaired carbon coating layer can effectively reduce the water absorption of the material surface; at the same time, the secondary carbon source sintering coating can effectively reduce the porosity between the materials and significantly improve the compaction performance of the material by re-agglomerating the fine powder in the material and increasing the contact area between the primary particles; in addition, the secondary carbon source sintering coating can improve the crystal structure of the material and improve the crystallinity of the crystal, thereby ensuring that the material has better cycle performance. In short, compared with the prior art, the preparation method of the present invention can effectively reduce the porosity of the material while reducing the powder resistance of the material, so that the material has high compaction performance, which is beneficial to improve the material's battery cell processing performance and the overall performance of the battery, and can further improve the crystallinity of the material crystal, thereby ensuring that the material has better cycle performance.

[0028] The sodium iron phosphate pyrophosphate composite material provided by the invention has the characteristics of high compaction and high conductivity.

[0029] The application of the sodium iron phosphate pyrophosphate composite material provided by the present invention is beneficial to improving the processing performance of the battery core and the overall performance of the battery.

[0030] The sodium ion battery provided by the present invention has excellent working performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1The XRD pattern of NFPP2-1 provided in Example 1 of the present invention;

[0033] Figure 2 This is the SEM image of NFPP2-1 provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] According to a first aspect of the present invention, there is provided a method for preparing a sodium iron phosphate pyrophosphate composite material, comprising the following steps:

[0036] The carbon-coated sodium iron phosphate pyrophosphate is solid-phase mixed with an organic carbon source and then sintered to obtain a sodium iron phosphate pyrophosphate composite material;

[0037] In the present invention, the solid phase mixing method includes but is not limited to at least one of ball milling, plowshare mixing, high-speed mixing and sand milling;

[0038] The temperature of the sintering process can be 400°C-580°C.

[0039] The preparation method of the sodium iron phosphate pyrophosphate composite material provided by the present invention comprises the following steps: solid-phase mixing carbon-coated sodium iron phosphate pyrophosphate (which can be understood as a sodium iron phosphate pyrophosphate material formed by sintering and coating a primary carbon source) with an organic carbon source, and then sintering treatment (which can be understood as secondary carbon source sintering and coating) is performed to obtain the sodium iron phosphate pyrophosphate composite material; on the one hand, after the secondary carbon source sintering and coating, the specific surface area of ​​the obtained composite material does not increase with the increase of carbon content, so that no side effects are produced on the processing of the battery core; on the other hand, through the secondary carbon source sintering and coating, It can make up for the defects of uneven primary carbon source coating, reduce the powder resistance of the material, effectively improve the uniformity of carbon coating, thereby improving the performance of the material. At the same time, the repaired carbon coating layer can effectively reduce the water absorption of the material surface; at the same time, the secondary carbon source sintering coating can effectively reduce the porosity between the materials and significantly improve the compaction performance of the material by re-agglomerating the fine powder in the material and increasing the contact area between the primary particles; in addition, the secondary carbon source sintering coating can improve the crystal structure of the material and improve the crystallinity of the crystal, thereby ensuring better cycle performance of the material.

[0040] In summary, compared with the prior art, the preparation method of the present invention can not only reduce the resistance of the material powder, but also effectively reduce the porosity of the material, so that the material has high compaction performance, which is beneficial to improve the material's battery cell processing performance and the overall performance of the battery, and can further improve the crystallinity of the material crystal, thereby ensuring that the material has better cycle performance.

[0041] In the present invention, carbon-coated sodium iron phosphate pyrophosphate (i.e., sodium iron phosphate pyrophosphate material formed by sintering and coating a primary carbon source) can be first subjected to air flow pulverization (gas pulverization) treatment, and the particle size of the material after gas pulverization is not particularly limited, and then solid-phase mixed with an organic carbon source, and then sintered after uniform mixing to carbonize the organic carbon source to achieve carbon coating of the material (which can be understood as achieving secondary carbon coating of the material); wherein the organic carbon source used for the secondary carbon coating includes but is not limited to at least one of glucose, starch, citric acid, vitamin C, polyethylene glycol, phenolic resin and sucrose.

[0042] In the present invention, the mass ratio of carbon-coated sodium ferric phosphate pyrophosphate to the organic carbon source can be (1-1.2): (0.01-0.05). The appropriate mass ratio of the two is not only more conducive to reducing the porosity, improving the compaction performance of the material and reducing the water absorption of the material, but also avoids the problem of excessive carbon content causing a significant reduction in the proportion of active substances and resulting in low electrochemical energy density.

[0043] In the present invention, typical but non-limiting temperatures for the sintering treatment are, for example, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 520°C, 540°C, 560°C, 580°C, and may be further preferably 500°C; typical but non-limiting times for the sintering treatment are, for example, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h.

[0044] The appropriate temperature and time of the sintering treatment can ensure that the organic carbon source is fully carbonized to form a carbon coating layer, thereby effectively realizing the secondary carbon coating of the material, fully repairing the damaged carbon layer on the surface of the material (for example, gas powder causes damage to the carbon layer on the surface of the material), and fully reducing the powder resistance of the material, while effectively reducing the porosity between the materials and improving the compaction performance of the material; if the sintering treatment temperature is too low, the organic carbon source cannot be fully decomposed, and the degree of graphitization decreases, which is not only not conducive to reducing the powder resistance of the material, but also increases the free carbon without electrochemical activity and reduces the gram capacity of the material; if the sintering treatment temperature is too high, it will cause the primary particles to break and produce microcracks, thereby deteriorating the structural stability of the material and affecting the cycle performance of the material; at the same time, too high a sintering temperature will cause the phase structure of the original material to change, resulting in a mixed phase with poor electrochemical performance or no electrochemical activity.

[0045] In a preferred embodiment, the heating rate of the sintering treatment may be 1°C / min-8°C / min, and typical but non-limiting heating rates are, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, and 8°C / min.

[0046] In a preferred embodiment, the chemical formula of the carbon-coated sodium iron phosphate is as follows:

[0047] Na x Fe y (PO4) z P2O7@C;

[0048] Among them, x can be between 3-6, for example, it can be 3, 4, 5 or 6, but not limited to this; y can be between 2-5, for example, it can be 2, 3, 4 or 5, but not limited to this; z can be between 1-4, for example, it can be 1, 2, 3 or 4, but not limited to this.

[0049] In a preferred embodiment, the preparation method of carbon-coated sodium iron phosphate pyrophosphate comprises the following steps:

[0050] The sodium source, the iron source, the phosphorus source and the carbon source are mixed and sand-milled and then spray-dried to obtain a precursor, and the precursor is calcined to obtain carbon-coated sodium iron phosphate pyrophosphate.

[0051] In the present invention, the particle size of the sodium source, iron source, phosphorus source and carbon source after mixed sand grinding can be 100nm-1000nm, and its typical but non-limiting particle size is, for example, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, and 1000nm.

[0052] A typical preparation method of a sodium iron phosphate pyrophosphate composite material comprises the following steps:

[0053] (a) Primary carbon source sintering coating: a sodium source, an iron source, a phosphorus source and a carbon source are mixed and sand-milled and then spray-dried to obtain a precursor, and the precursor is calcined to obtain carbon-coated sodium iron phosphate pyrophosphate;

[0054] (b) air flow pulverization: air flow pulverizing the carbon-coated sodium ferric phosphate pyrophosphate obtained in step (a) to obtain an air-pulverized material;

[0055] (c) Secondary carbon source sintering coating: solid-phase mixing the gas-powdered material obtained in step (b) with an organic carbon source, which may be performed by mechanical stirring to obtain a mixed material;

[0056] Wherein, the organic carbon source includes but is not limited to at least one of glucose, starch, citric acid, vitamin C, polyethylene glycol, phenolic resin, polystyrene and sucrose;

[0057] The mixed material is sintered, and then crushed and sieved to obtain the final modified sodium iron phosphate pyrophosphate material, that is, the sodium iron phosphate pyrophosphate composite material.

[0058] The present invention can ensure that the carbon source is evenly distributed in the material through the steps of secondary carbon source sintering and coating, thereby avoiding the problem of material performance being affected by uneven carbon coating; during the secondary carbon source sintering and coating process, the organic carbon source is carbonized during the sintering process, which can repair the damage caused by gas powder to the carbon layer on the surface of the material, not only can the powder resistance of the material be effectively reduced, but also the porosity between the materials can be effectively reduced by re-agglomerating the fine powder in the material, and the compaction performance of the material can be significantly improved; in short, the secondary carbon source sintering and coating makes up for the defect of uneven primary carbon source coating, further reduces the powder resistance of the material, and also increases the contact area between the primary particles, effectively reduces the porosity between the materials, and significantly improves the compaction performance of the material; in addition, the secondary carbon source sintering and coating can improve the crystal structure of the material, improve the crystallinity of the crystal, and ensure that the material has better cycle performance; it can be seen that the preparation method provided by the present invention effectively solves the technical problems in the prior art such as uneven carbon source coating, difficulty in effectively reducing the porosity between materials, failure to significantly improve the compaction performance of the material, and possible changes in the crystal structure of the material.

[0059] At the same time, it should be noted that although there are technical solutions for the secondary carbon source sintering coating of lithium iron phosphate in the prior art, since the lithium iron phosphate system is different from the sodium iron pyrophosphate system, it is impossible to predict what technical effects or performance levels the sodium iron pyrophosphate can achieve after the secondary carbon source sintering coating of lithium iron phosphate.

[0060] According to a second aspect of the present invention, there is provided a sodium iron phosphate pyrophosphate composite material, which is prepared by any of the preparation methods described above.

[0061] The sodium iron phosphate pyrophosphate composite material provided by the invention has the characteristics of high compaction and high conductivity, the battery core processing performance of the material is significantly improved, and the electrochemical performance of the material is effectively improved.

[0062] According to a third aspect of the present invention, there is provided a use of the above-mentioned sodium iron phosphate pyrophosphate composite material in a positive electrode material for a battery.

[0063] The application of the sodium iron phosphate pyrophosphate composite material provided by the present invention is beneficial to improving the processing performance of the battery core and the overall performance of the battery.

[0064] The sodium iron phosphate pyrophosphate composite material of the present invention can be widely used in the fields of electric vehicles, energy storage systems, and portable electronic devices. With the growing global demand for clean energy, the electric vehicle market is developing rapidly, and sodium iron phosphate pyrophosphate, as a battery positive electrode material with high energy density and long cycle life, has huge market demand. At the same time, as an important component of new energy, the energy storage system also plays an important role in improving the stability and reliability of the power grid. In addition, portable electronic devices such as smart phones and tablets also have higher requirements for battery life and charging speed, and sodium iron phosphate materials can effectively improve the performance of these devices. Therefore, the sodium iron phosphate pyrophosphate composite material of the present invention has broad market prospects and application needs.

[0065] According to a fourth aspect of the present invention, a sodium ion battery is provided, wherein the positive electrode of the sodium ion battery comprises the sodium iron phosphate pyrophosphate composite material described above.

[0066] The sodium ion battery provided by the present invention has excellent working performance.

[0067] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0068] Example 1

[0069] A method for preparing a sodium iron phosphate pyrophosphate composite material comprises the following steps:

[0070] (a) Primary carbon source sintering coating: disodium hydrogen phosphate, ferric phosphate, ferrous oxalate and starch are mixed and sand-ground to a particle size of 500 nm and then spray-dried to obtain a precursor, which is then calcined at a temperature of 500°C for 6 h to obtain carbon-coated sodium iron phosphate pyrophosphate, whose chemical formula is Na3Fe2(PO4)P2O7@C;

[0071] (b) air flow milling: the carbon-coated sodium ferric phosphate pyrophosphate obtained in step (a) is subjected to air flow milling to a particle size of 4 μm to 8 μm to obtain an air-pulverized material (denoted as NFPP1);

[0072] (c) Secondary carbon source sintering coating: The gas-powdered material (NFPP1) obtained in step (b) was solid-phase mixed with starch in a mass ratio of 1:0.01, and mixed evenly by mechanical stirring (stirring speed 500 rpm, stirring time 30 min) to obtain a mixed material;

[0073] The mixed material was sintered in nitrogen atmosphere at 500°C (heating rate 5°C / min) and 1h of sintering holding time. After sintering, the material was crushed (crusher speed 1000rpm) and sieved (sieve mesh 100 mesh) to obtain the final modified sodium iron phosphate pyrophosphate material, i.e., sodium iron phosphate pyrophosphate composite material, denoted as NFPP2-1. Its XRD and SEM images are shown in Figure 1 and Figure 2 .

[0074] Example 2

[0075] The difference between this embodiment and embodiment 1 is that in step (c), the sintering temperature is 400°C;

[0076] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-2).

[0077] Example 3

[0078] The difference between this embodiment and embodiment 1 is that in step (c), the sintering temperature is 450°C;

[0079] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-3).

[0080] Example 4

[0081] The difference between this embodiment and embodiment 1 is that in step (c), the sintering temperature is 550°C;

[0082] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-4).

[0083] Example 5

[0084] The difference between this embodiment and embodiment 1 is that in step (c), the sintering temperature is 580°C;

[0085] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-5).

[0086] Example 6

[0087] The difference between this embodiment and embodiment 1 is that in step (c), the sintering holding time is 0.5 h;

[0088] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-6).

[0089] Example 7

[0090] The difference between this embodiment and embodiment 1 is that in step (c), the sintering holding time is 1.5 h;

[0091] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron phosphate pyrophosphate composite material (NFPP2-7).

[0092] Example 8

[0093] The difference between this embodiment and embodiment 1 is that in step (c), the sintering holding time is 2h;

[0094] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-8).

[0095] Example 9

[0096] The difference between this embodiment and embodiment 1 is that in step (c), the sintering holding time is 3h;

[0097] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-9).

[0098] Example 10

[0099] The difference between this embodiment and embodiment 1 is that in step (c), the gas-powdered material (NFPP1) and starch are solid-phase mixed at a mass ratio of 1.2:0.01;

[0100] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron phosphate pyrophosphate composite material (NFPP2-10).

[0101] Embodiment 11

[0102] The difference between this embodiment and embodiment 1 is that in step (c), the gas-powdered material (NFPP1) and starch are solid-phase mixed at a mass ratio of 1:0.05;

[0103] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron phosphate pyrophosphate composite material (NFPP2-11).

[0104] Example 12

[0105] The difference between this embodiment and embodiment 1 is that in step (c), starch is replaced by citric acid;

[0106] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-12).

[0107] Embodiment 13

[0108] The difference between this embodiment and embodiment 1 is that in step (c), starch is replaced by polyethylene glycol;

[0109] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron phosphate pyrophosphate composite material (NFPP2-13).

[0110] Embodiment 14

[0111] The difference between this embodiment and embodiment 1 is that in step (c), starch is replaced with sucrose;

[0112] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron phosphate pyrophosphate composite material (NFPP2-14).

[0113] Embodiment 15

[0114] The difference between this embodiment and embodiment 1 is that the chemical formula of the carbon-coated sodium iron phosphate pyrophosphate obtained in step (a) is Na4Fe3(PO4)2P2O7@C (denoted as NFPP4);

[0115] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP4-2).

[0116] Example 16

[0117] The difference between this embodiment and embodiment 1 is that the chemical formula of the carbon-coated sodium iron phosphate pyrophosphate obtained in step (a) is Na5Fe4(PO4)3P2O7@C (denoted as NFPP5);

[0118] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron phosphate pyrophosphate composite material (NFPP5-2).

[0119] Comparative Example 1

[0120] The difference between this comparative example and Example 1 is that in step (c), the solid phase mixing is replaced by wet ball milling mixing;

[0121] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron phosphate pyrophosphate composite material (NFPP2-Comparison 1).

[0122] Comparative Example 2

[0123] The difference between this comparative example and Example 1 is that in step (c), the gas-powdered material (NFPP1) is not mixed with starch, that is, the NFPP1 is directly sintered;

[0124] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron phosphate pyrophosphate composite material (NFPP2-comparison 2).

[0125] Comparative Example 3

[0126] The difference between this comparative example and Example 1 is that in step (c), the sintering temperature is 650°C;

[0127] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-comparison 3).

[0128] Comparative Example 4

[0129] The difference between this comparative example and Example 1 is that in step (c), the sintering temperature is 350°C;

[0130] The remaining steps and process parameters are the same as those in Example 1 to obtain a sodium iron pyrophosphate composite material (NFPP2-comparison 4).

[0131] Test example

[0132] The electrical properties and physicochemical properties of the sodium iron pyrophosphate composite materials obtained in the examples and comparative examples were tested.

[0133] The electrical performance test method is as follows:

[0134] The active material, conductive agent and binder are mixed in a mass ratio of 8:1:1 to form a positive electrode slurry, which is then coated on an aluminum foil to form a positive electrode. A sodium sheet is used as the negative electrode to form a button-type half-cell, which is tested on a Xinwei electrochemical tester with a nominal specific capacity of 120mAh / g. It is cycled at rates of 0.1, 0.2, 0.5, 1, 2, and 5, and is cycled at 1C constant current and constant voltage.

[0135] Physical and chemical properties test methods:

[0136] The powder compaction test method is carried out according to the compaction test method in the appendix of the national standard GB / T24533-2009. A certain amount of powder to be tested is weighed and put into the mold of the powder compaction density instrument. The main pressure is increased to 3 tons by gradually applying pressure, and the parameters are recorded.

[0137] The test of powder resistance mainly adopts the two-probe test method. The test electrodes are placed on the upper and lower sides of the sample respectively. By applying the excitation current, the voltage on the upper and lower sides of the sample is detected, and finally the overall resistance of the sample is obtained. The resistivity of the sample can be converted by the sample molding size.

[0138] The test method for specific surface area is mainly based on the volumetric method for determining the BET specific surface area of ​​powder specified in GB / T19587.

[0139] The test results of the composite materials obtained in Examples 1-14 are shown in Table 1, the test results of the composite materials obtained in Example 15 are shown in Table 2, the test results of the composite materials obtained in Example 16 are shown in Table 3, and the test results of the composite materials obtained in Comparative Examples 1-4 are shown in Table 4.

[0140] Table 1

[0141] Material Discharge specific capacity (mAh / g) <![CDATA[Compaction performance (g / cm 3 )]]> Powder resistance (μΩ·m) <![CDATA[Specific surface area (m 2 / g)]]> NFPP1 112.4 1.85 8576040 12.089 NFPP2-1 121.8 2.15 785900 11.512 NFPP2-2 114.3 2.08 4534020 12.034 NFPP2-3 118.3 2.11 1034680 11.822 NFPP2-4 116.9 2.16 776810 11.501 NFPP2-5 113.1 2.15 773670 11.703 NFPP2-6 114.7 2.05 2012870 11.924 NFPP2-7 120.2 2.14 789600 12.018 NFPP2-8 120.8 2.15 798000 12.023 NFPP2-9 117.9 2.13 896710 12.015 NFPP2-10 115.6 2.09 1778800 11.010 NFPP2-11 111.6 1.98 769800 12.542 NFPP2-12 113.8 2.02 924600 12.028 NFPP2-13 121.3 1.95 842500 12.031 NFPP2-14 114.1 2.01 837010 12.034

[0142] Table 2

[0143] Material Discharge specific capacity (mAh / g) <![CDATA[Compaction performance (g / cm 3 )]]> Powder resistance (μΩ·m) <![CDATA[Specific surface area (m 2 / g)]]> NFPP4 112.7 1.95 2980100 10.898 NFPP4-2 118.6 2.18 876000 10.758

[0144] Table 3

[0145] Material Discharge specific capacity (mAh / g) <![CDATA[Compaction performance (g / cm 3 )]]> Powder resistance (μΩ·m) <![CDATA[Specific surface area (m 2 / g)]]> NFPP5 124.5 1.88 1267000 11.89 NFPP5-2 129.3 1.99 893400 11.73

[0146] Table 4

[0147] Material Discharge specific capacity (mAh / g) <![CDATA[Compaction performance (g / cm 3 )]]> Powder resistance (μΩ·m) <![CDATA[Specific surface area (m 2 / g)]]> NFPP1 112.4 1.85 8576040 12.089 NFPP2-Comparison 1 102.2 1.92 10278400 13.982 NFPP2-Comparison 2 112.8 1.86 8434590 12.087 NFPP2-Comparison 3 88.1 2.16 452700 12.017 NFPP2-Comparison 4 111.7 1.93 2318900 12.367

[0148] By comparing the result data of Examples 1-5, it can be seen that in the secondary carbon source sintering and coating process, too low a sintering temperature cannot fully carbonize the organic carbon source, resulting in an excessive proportion of free carbon, which not only makes it difficult to effectively reduce the powder resistance, but also reduces the proportion of active substances and reduces the gram capacity; at the same time, too high a sintering temperature will destroy the structure of the material and lead to deterioration of the electrochemical performance.

[0149] By comparing the result data of Examples 1 and 6-9, it can be seen that in the process of sintering and coating the secondary carbon source, the sintering time is too short, resulting in incomplete carbonization, which will not only bring excess uncarbonized impurities and reduce the gram capacity, but also have a low effect on improving other physical properties of the material; although sintering time that is too long can also improve various aspects of the material's performance, too long a time wastes energy and increases the cost of the material; it can be seen that the appropriate sintering time also plays an important role in the impact on the material.

[0150] By comparing the result data of Examples 1 and 10-11, it can be seen that the amount of organic carbon source used mainly affects the physical properties of the material. The specific surface area of ​​the material is greatly affected by the carbon content. The larger the carbon content, the larger the specific surface area of ​​the material. The larger specific surface area of ​​the material is not conducive to the processing stage of the battery cell slurry. Therefore, a reasonable amount of organic carbon source used can make the overall performance of the material more excellent.

[0151] By comparing the result data of Examples 1 and 12-14, it can be seen that different organic carbon sources have different effects on the materials. The main reason is that different organic carbon sources have different carbonization temperatures, different molecular chains, different special functional groups and different mixed dispersion states. By comparing several different organic carbon sources, it was found that starch has a more positive effect on improving the various properties of the material.

[0152] It can be seen from the result data of Example 15 and Example 16 that the optimization of material performance by the method of the present invention is not only for one type of sodium iron pyrophosphate, but also has the effect of optimizing the performance of a variety of sodium iron pyrophosphate materials with different sodium-iron-phosphorus ratios.

[0153] By comparing the result data of Example 1 with that of Comparative Example 1, it can be seen that the defect of Comparative Example 1 is that, on the one hand, wet ball milling will destroy the carbon coated on the surface of the material once, and at the same time increase the intrinsic water absorption of the material; on the other hand, wet ball milling will inevitably lead to the individual agglomeration of organic carbon, affecting its dispersion uniformity, reducing the effect of secondary carbon coating, and thus resulting in almost no improvement in powder resistance, compaction performance, etc.

[0154] By comparing the result data of Example 1 with that of Comparative Example 2, it can be seen that if no additional organic carbon source is added for secondary calcination, the modification effect on the material is not obvious, indicating that the organic carbon source plays a very important role in the secondary calcination process.

[0155] By comparing the result data of Example 1 with that of Comparative Example 3, it can be seen that the defect of Comparative Example 3 is that, on the one hand, the sintering temperature is too high, which will cause the primary particles to break and produce microcracks, thereby deteriorating the structural stability of the material and affecting the cycle performance of the material; on the other hand, the excessively high sintering temperature will cause the phase structure of the original material to change, resulting in a miscellaneous phase with poor electrochemical performance or no electrochemical activity, causing the discharge specific capacity of the material to decrease from 112.4 mAh / g of NFPP1 to 88.1 mAh / g.

[0156] By comparing the result data of Example 1 with that of Comparative Example 4, it is shown that a sintering temperature that is too low will result in the inability to effectively decompose and carbonize the organic carbon source. This not only has no obvious effect on improving the powder resistance, but the increased carbon also reduces the proportion of active substances in the material, affecting the electrochemical performance. At the same time, the increased carbon is mostly free carbon, which also increases the specific surface area of ​​the material.

[0157] It can be seen that the preparation method provided by the present invention is simple, efficient and has a high success rate. It can not only improve the uniformity of carbon source coating, effectively reduce the powder resistance and porosity of the material, and significantly improve the compaction performance of the material, but also the secondary coated carbon can effectively block the reaction between the surface of the material and water in the air, thereby reducing the water absorption of the material. At the same time, the process method can also avoid changes in the crystal structure of the material, thereby comprehensively improving the performance of the material.

[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a sodium iron phosphate pyrophosphate composite material, characterized in that: The following steps are involved: The carbon-coated sodium iron phosphate pyrophosphate is solid-phase mixed with an organic carbon source and then sintered to obtain the sodium iron phosphate pyrophosphate composite material; The sintering temperature is 400°C-580°C.

2. The preparation method according to claim 1, characterized in that: The heating rate of the sintering process is 1°C / min-8°C / min; The holding time of the sintering treatment is 0.5h-3h.

3. The preparation method according to claim 2, characterized in that: The sintering temperature is 500°C.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The chemical formula of the carbon-coated sodium iron pyrophosphate is as follows: So x Feb y (PO4) z P2O7@C; Among them, x is between 3-6, y is between 2-5, and z is between 1-4.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation method of the carbon-coated sodium ferric phosphate pyrophosphate comprises the following steps: The sodium source, the iron source, the phosphorus source and the carbon source are mixed and sand-milled and then spray-dried to obtain a precursor, and the precursor is calcined to obtain carbon-coated sodium iron phosphate pyrophosphate.

6. The preparation method according to claim 5, characterized in that: The particle size after sand grinding is 100nm-1000nm.

7. The preparation method according to any one of claims 1 to 3, characterized in that: The organic carbon source includes at least one of glucose, starch, citric acid, vitamin C, polyethylene glycol, phenolic resin, polystyrene and sucrose.

8. A sodium iron phosphate pyrophosphate composite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the sodium iron phosphate pyrophosphate composite material according to claim 8 in a positive electrode material for a battery.

10. A sodium ion battery, characterized in that: The positive electrode of the sodium ion battery comprises the sodium iron phosphate pyrophosphate composite material according to claim 8.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery positive electrode material Na3Fe2 (PO4) P2O7

    CN115611258A

  • Nitrogen-doped mesoporous carbon coated ferric sodium pyrophosphate composite material and preparation method thereof

    CN115974033A

  • Sodium-ion battery positive electrode material and preparation method thereof

    CN115986080A

  • Carbon-coated ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN116230923A

  • Carbon composite pyrophosphoric acid and sodium ferric phosphate composite material, preparation thereof and application of composite material in sodium ion battery

    CN116487545A

Cited By

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof and battery

    CN119528107A

  • Modified composite sodium ferric phosphate positive electrode material and preparation method and application thereof

    CN120646797A

  • High-solid-degree composite sodium ferric phosphate positive electrode material, preparation method thereof and battery

    CN121063508A

  • A high-solidity composite sodium iron phosphate positive electrode material, a preparation method thereof and a battery

    CN121063508B